Prediction of dynamic recrystallization behavior of SAE52100 large section bearing steel based on machine learning - Peiheng Ding; Changqing Shu; Shasha Zhang; Zhaokuan Zhang; Xingshuai Liu; Jicong Zhang; Qian Chen; Shuaipeng Yu; Xiaolin Zhu; Zhengjun Yao (Materials Genome Engineering Advances, 2024)
Abstract This paper investigates the dynamic recrystallization characteristics of SAE52100 large section bearing steel under hot compression, focusing on both the center and surface. Using data from thermal simulation experiments the physical models were developed. Four machine learning algorithms including support vector regression, k‐nearest neighbors, random forest, and extreme gradient boosting were then employed to develop dynamic recrystallization prediction models based on the experimental data and inferred values from the physical model. The results show that the machine learning methods provide a better numerical description of the model, provided these are fed with extensive data. To enhance the scope of application, we obtained data from the dynamic recrystallization models for both the center and surface of SAE52100 steel in the as‐cast state, as well as extrapolated values from the literature regarding the hot‐rolled condition. When the SHAP method was introduced to reveal the mechanism of the influence of each input feature on the prediction results of the machine learning model, it was found that the test results of the Cr element did not match the theory, mainly because of the small scale of Cr elemental data and the strong dependence on grain size and secondary dendrite spacing.